Perhitungan Energi Kinetik Pada Sistem Pengereman Regenerative Mobil Listrik - Triwahju Hardianto; Hari Sutjahjono; M. Edoward Ramadhan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2015)
This research is early step of the research developing on regenerative breaking system of Jember University electric car. This research focuses on the energy recovery system application using kinetic energy on electrical while do breaking. Application of KERS (Kinetic Energy Recovery System) is expected to improve the performance of electrical energy storage systems and increase the mileage of electric cars with regenerative system on the battery charging system.The regenerative braking system in this research is to create a prototype system that consists of three main components namely CVT (continuously variable transmission), flywheel and clutch. Data obtained on the experimental results showed that the relationship parameters i.e. car wheel speed, the flywheel speed and duration of the flywheel during braking. At one of the results of data is obtained wheel speed data of 680 rpm, speed flywheel of 128 rpm with duration of flywheel rotation after braking of 21.42 seconds.